Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1074/jbc.m403581200
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Biologically Active Oxysterols during Ozonolysis of Cholesterol Present in Lung Surfactant

Abstract: Exposure of the lung to concentrations of ozone found in ambient air is known to cause toxicity to the epithelial cells of the lung. Because of the chemical reactivity of ozone, it likely reacts with target molecules in pulmonary surfactant, a lipid-rich material that lines the epithelial cells in the airways. Phospholipids containing unsaturated fatty acyl groups and cholesterol would be susceptible to attack by ozone, which may lead to the formation of cytotoxic products. Whereas free radicalderived oxidized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
102
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 54 publications
2
102
2
Order By: Relevance
“…ceptible to ozone due to the presence of ozone in the troposphere and therefore present in air inspired into the lung. Recent studies have revealed the formation of two major products when low concentrations (100 -500 ppb) of ozone (such levels can be present in the air of large cities, to which humans are exposed on a constant basis) were exposed to lung surfactant (20). The initial reaction of ozone is the addition across the ⌬ 5 -double bond of Ch, which yields a 1,2,3-trioxolane that undergoes rapid and spontaneous decomposition to yield several additional reactive entities, including carbonyl oxides, carbon-centered radicals, and hydroperoxides, which ultimately lead to the cleavage of the C-5-C-6 double bond (Fig.…”
Section: Nonradical Pathways ( 1 O 2 O 3 Hocl)mentioning
confidence: 99%
“…ceptible to ozone due to the presence of ozone in the troposphere and therefore present in air inspired into the lung. Recent studies have revealed the formation of two major products when low concentrations (100 -500 ppb) of ozone (such levels can be present in the air of large cities, to which humans are exposed on a constant basis) were exposed to lung surfactant (20). The initial reaction of ozone is the addition across the ⌬ 5 -double bond of Ch, which yields a 1,2,3-trioxolane that undergoes rapid and spontaneous decomposition to yield several additional reactive entities, including carbonyl oxides, carbon-centered radicals, and hydroperoxides, which ultimately lead to the cleavage of the C-5-C-6 double bond (Fig.…”
Section: Nonradical Pathways ( 1 O 2 O 3 Hocl)mentioning
confidence: 99%
“…It is not known if some of these occur naturally, and there is a need for methods to make comprehensive studies of the nature and levels of oxysterols in tissues and body fluids. This is illustrated by the recent identification of novel oxysterols, formed from cholesterol by the action of ozone, in human tissues [27][28][29][30]. Evidence has been presented for their involvement in the mediation of inflammatory processes associated with the development of atherosclerotic lesions [28], and in the initiation of protein misfolding as occurs in several neurological diseases [29].…”
mentioning
confidence: 99%
“…The levels of the 5,6-secosterol and its aldol were surprisingly high in brain of patients with Alzheimer's disease and healthy subjects [combined seco-sterol levels ϳ0.44 pmol/mg (ϳ180 ng/g) and ϳ0.35 pmol/mg (ϳ150 ng/g), respectively]. Biologically active oxysterols are also formed during ozonolysis of cholesterol in lung surfactant [30]. Pulfer and Murphy [30] identified the major cholesterol derived ozonolysis product in lung surfactant as 5␤,6␤-epoxycholesterol (C-3␤-ol-5␤,6␤-epoxide).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxysterols are oxygenated derivatives of cholesterol and important constituents of oxidized low density lipoproteins that are detected in association with surfactant during acute lung injury (4). Oxysterols are present in human lung and exert potent biological effects by controlling expression of diverse genes via binding to liver X receptors (LXRs), members of the nuclear receptor superfamily (5,6).…”
mentioning
confidence: 99%